Islamic Principles of Justice in Cross-Cultural Business Transactions: A Phenomenological Study in Indonesian Multicultural Business Context - Sudana, Sudana; Marpuah, Marpuah; Dermawan, Muhammad Jagat; Samudra, Muhammad Gilang; Alfaqih, Mujahid 'Ayyasy (Kawanua International Journal of Multicultural Studies, 2024)
The principle of justice is a fundamental value in Islamic economics that is relevant to be applied in cross-cultural transactions. However, differences in cultural values and social backgrounds can affect its implementation. This study aims to explore the application of the principle of Islamic justice in cross-cultural transactions in a multicultural society. The study used a qualitative method with a phenomenological approach, while data analysis was carried out using NVivo software. Data were obtained through interviews with cross-cultural business actors and analyzed through thematic coding. The findings show that the principle of justice includes honesty, transparency, and equality in the treatment of all parties, which contribute to the creation of more harmonious and mutually beneficial business relationships. However, its implementation faces challenges in the form of different perceptions of justice, imbalance of information, and the influence of local cultural norms. The flexible and inclusive principle of Islamic justice provides a strong foundation to overcome these challenges and create harmony in cross-cultural transactions.